IMPLEMENTASI PENDIDIKAN KARAKTER SISWA KELAS V DI SD NEGERI 6 DAWUHAN KABUPATEN SITUBONDO TAHUN PELAJARAN 2017/2018 - Rindi Rahmawati Istiqomaria; Aenor Rofek (Jurnal IKA PGSD (Ikatan Alumni PGSD) UNARS, 2019)
The implementation of character education is through habituation, namely three religious values, discipline values, and environmental care values. Whereas the learning of character values ​​through habituation in SD Negeri 6 Dawuhan, Situbondo District is carried out through programmed activities, routine activities, and spontaneous activities. This study aims to determine the implementation of the implementation of character education for fifth grade students at SD Negeri 6 Dawuhan, Situbondo, 2017/2018 school year, and the subjects of this study were all fifth grade students of SD Negeri 6 Dawuhan, Situbondo, 2017/2018 Academic Year with the number of respondents 34 student. The school is the total sample of 208 students.This study included a qualitative descriptive study. Data sources use primary data and secondary data, while the technique for determining informants is 4 people. Data retrieval method uses observation, interviews, questionnaires, documentation. Data analysis techniques used are data collection, data reduction, data presentation and conclusion drawing. While to test the validity of the data the researcher used observation persistence and triangulation techniques